2011
DOI: 10.1371/journal.pone.0017043
|View full text |Cite
|
Sign up to set email alerts
|

Low CD4+ T Cell Counts among African HIV-1 Infected Subjects with Group B KIR Haplotypes in the Absence of Specific Inhibitory KIR Ligands

Abstract: Natural killer (NK) cells are regulated by interactions between polymorphic killer immunoglobulin-like receptors (KIR) and human leukocyte antigens (HLA). Genotypic combinations of KIR3DS1/L1 and HLA Bw4-80I were previously shown to influence HIV-1 disease progression, however other KIR genes have not been well studied. In this study, we analyzed the influence of all activating and inhibitory KIR, in association with the known HLA inhibitory KIR ligands, on markers of disease progression in a West African popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
13
2
Order By: Relevance
“…In contrast, some studies also indicated negative effects of increased NK cell activation on HIV-1/SIV pathogenesis. For example, combinations of KIR and HLA genotypes that favor NK cell activation were shown to play a detrimental role in HIV-1 disease progression (38). Furthermore, low levels of antiviral activation and a lower frequency of protective activating KIRs were reported in a group of rare HIV-1-infected controllers (39).…”
Section: Cd8␣mentioning
confidence: 99%
“…In contrast, some studies also indicated negative effects of increased NK cell activation on HIV-1/SIV pathogenesis. For example, combinations of KIR and HLA genotypes that favor NK cell activation were shown to play a detrimental role in HIV-1 disease progression (38). Furthermore, low levels of antiviral activation and a lower frequency of protective activating KIRs were reported in a group of rare HIV-1-infected controllers (39).…”
Section: Cd8␣mentioning
confidence: 99%
“…[15][16][17][18][19] KIR/HLA combinations influence the rate of HIV-1 disease progression. [20][21][22][23][24][25][26][27] Studies of HIV-exposed seronegative (HESN) individuals also showed an effect of KIR/HLA genetic variation on susceptibility to HIV-1 acquisition, [28][29][30][31][32][33][34] with several of those reporting KIR/HLA combinations with an NK cell activating profile to be characteristic of HESN subjects. [28][29][30]32 To date, no study has investigated the impact of allogeneic KIR/HLA combinations across sexual partners on HIV-1 transmission.…”
Section: Introductionmentioning
confidence: 99%
“…5 Notably, autoantigen-specific cytotoxic CD8 + T cells expressing inhibitory KIRs have been isolated from human blood. [21][22][23] It is therefore conceivable that KIR-mediated inhibitory signals such as those provided by KIR2DL3 regulate NK-and T-cell activation during autoimmune responses in MS. 5,24,25 We observed that individuals carrying two copies for KIR2DL2 but lacking KIR2DL3 were overrepresented in the CIS/MS cohort. Similarly, the frequency of KIR2DL3-negative donors homozygous for KIRD2DS2, with which KIR2DL2 shares strong linkage disequilibrium, was significantly higher in the CIS/MS cohort.…”
Section: Discussionmentioning
confidence: 72%